Signed, Sealed, Delivered: Microenvironmental Modulation of Extracellular Vesicle-Dependent Immunoregulation in the Lung - Schneider, Daniel J.; Speth, Jennifer M.; Peters-Golden, Marc (Frontiers in Cell and Developmental Biology, 2016)
Unconventional secretion and subsequent uptake of molecular cargo via extracellular vesicles (EVs) is an important mechanism by which cells can exert paracrine effects. While this phenomenon has been widely characterized in the context of their ability to promote inflammation, less is known about the ability of EVs to transfer immunosuppressive cargo. Maintenance of normal physiology in the lung requires suppression of potentially damaging inflammatory responses to the myriad of insults to which it is continually exposed. Recently, our laboratory has reported the ability of alveolar macrophages (AMs) to secrete suppressors of cytokine signaling (SOCS) proteins within microvesicles (MVs) and exosomes (Exos). Uptake of these EVs by alveolar epithelial cells (AECs) resulted in inhibition of pro-inflammatory STAT activation in response to cytokines. Moreover, AM packaging of SOCS within EVs could be rapidly tuned in response to exogenous or AEC-derived substances. In this article we will highlight gaps in knowledge regarding microenvironmental modulation of cargo packaging and utilization as well as EV secretion and uptake. Advances in these areas are critical for improving understanding of intercellular communication in the immune system and for therapeutic application of artificial vesicles aimed at treatment of diseases characterized by dysregulated inflammation.